Determinacion de factores antinutritivos termorresistentes en leguminosas. III. Fitatos - Cuadrado, C.=700 1 Muzquiz, M.; Robredo, L.M.; Ayet, G.; Burbano, C.
(Es, En)
ilus., 16 ref.
Keywords: ACIDO FITICO; INOSITOL; LEGUMINOSAS; ESPAÑA; MIO-INOSITOL